Body composition and mortality in a cohort study of Chinese patients with hypertrophic cardiomyopathy - Zhou, Ke; Xiang, Jie; Li, Guo-yong; Pu, Xiao-bo; Zhang, Li (Frontiers in Cardiovascular Medicine, 2023)
Objective To analyse the characteristics and mortality of hypertrophic cardiomyopathy (HCM) patients with different body compositions. Methods In this study, 530 consecutive patients with HCM at West China Hospital were studied from November 2008 to May 2016. An equation based on body mass index (BMI) was used to obtain the Percent body fat (BF) and lean mass index (LMI). Patients were divided into five sex-specific BMI, BF and LMI quintiles. Results The average BMI, BF and LMI were 23.1 ± 3.2 kg/m2, 28.1 ± 7.3% and 16.5 ± 2.2 kg/m2, respectively. Patients with higher BMI or BF were older and had more symptoms and adverse cardiovascular conditions; those with higher LMI were younger and had less coronary artery disease and lower serum NT-proBNP and creatine. BF correlated positively with resting left ventricular (LV) outflow tract gradient, mitral regurgitation (MR) degree and left atrial diameter but was inversely associated with septal wall thickness (SWT), posterior wall thickness (PWT), LV mass, and E/A ratio; LMI was positively correlated with SWT, LV end diastolic volume and LV mass but was negatively associated with MR degree.48 all-cause deaths occurred during a median follow-up of 33.8 months. Reversed J-shape associations of BMI and LMI with mortality were observed. A lower BMI or LMI was significantly associated with high mortality, especially for low-moderate BMI and LMI. No significant difference in mortality was found across BF quintiles. Conclusions The associations of BMI, BF and LMI with baseline characteristics and cardiac remodelling are different in HCM patients. In Chinese HCM patients, low BMI and LMI predicted mortality but not BF.